MANUSIA DAN KESEMPURNAANNYA : (TELAAH PSIKOLOGI TRANSENDENTAL MULLĀ SHADRĀ) - Kerwanto (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2015)
Mullā Ṣadrā is one of the philosophers who had considerable attention to the study of human. His view concerning the human soul and its perfection can be applied as the basis of Islamic principles of psychology. Under the investigation on his philosophical writtings as well as his Quranic interpretation, such as Tafsīr al-Qur’ān, we are invited to understand human nature and its perfection. This article shows Ṣadra’s view about the value of knowledge as the basis of the achievement of happiness in human being. This paper also intended to show that knowledge about the reality of the human soul has a major influence on moral action of an individual